Politics and Intertextuality in Juara: (Politik dan Intertekstualiti dalam Juara) (Malay Literature, 2016)
This article focuses on the interrelationship between texts in Malay novels, and the processes that take place related to intertextuality. For the framework of this study, the intertextuality theory of Julia Kristeva was used. This theory is concerned with the relationship between the hypotext (short story) and hypertext (novel) in order to study meaning, the process presented and the author's rationale. This study focuses on the writings of S. Othman Kelantan, who appears to have a tendency towards producing intertextual works, focusing on his novel Juara. The study reveals that with reference to intertextuality, the writings of S. Othman Kelantan display a loyalty towards the prior text, as well as to the short story genre. Juara, which is an expansion from the short story "Pahlawan Lembu", is an example of this. The style of S. Othman Kelantan's writing reveal his sensitivity towards the contemporary political climate; his conviction and ideology is presented in metaphor in Juara. The intertextual relationship between the short story and the novel Juara is evident in both theme and plot. The writer employs transformation, extension and modification, influenced by several factors including environment, personal background and his own life experience.Keywords: S. Othman Kelantan, Juara, "Pahlawan Lembu", Julia Kristeva, intertextuality